PENGEMBANGAN MODUL DIGITAL BERBASIS TEAM LEARNING PADA VIRTUAL CLASSROOM KONSEP DASAR IPS SD - Endah Marwanti; Wardani, Kristi; Megawati, Ida (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to develop a digital module based on team learning for elementary social studies basic concepts. The research method used is a research and development method. The population in the study were PGSD students at the University of Sarjanawiyata Tamansiswa Yogyakarta in class 2A and 2D in the Even Semester 2020/2021. The sample used in this study used saturated sampling. Data collection techniques were carried out by distributing questionnaires to respondents. Data analysis was carried out descriptively with a frequency distribution table. The results of this research are 1) defining stage, 2) planning, 3) development, and 4) dissemination. In the definition stage, it is done by analyzing students, namely students, curriculum analysis, and material analysis. The planning stage is the selection of formats, the design of teaching materials. This development stage is carried out through validation and testing. While at the dissemination stage by conducting a seminar on results at PGSD.